Literature Review: Perbedaan Waktu Reaksi antara Pemain Voli dan Pemain Basket - Rafida Ikhsania Camalis; Asnawati Asnawati; Dona Marisa (Homeostasis, 2021)
Abstract: Basketball and volleyball are sports that require quick reactions in their game, these two sports have some similarities in technical motion. Writing this literature review aim to summarize the comparison of reaction times between volleyball players and basketball players. The method used is the narrative review method, namely by using articles obtained through a literature search process. The writing was conducted by analyzing related literature obtained from the search results on medical journal databases, such as PubMed and Google Scholar. Included articles are in English and published in 2009-2020. The review included 5 articles. Based on the five articles, there is a significant difference in reaction time between the reaction time of volleyball players and basketball players’ reaction time, with the reaction time values obtained faster for basketball players than for volleyball players. Significant or not the difference in reaction time is influenced by several factors, such as arousal, age, exercise intensity, fatigue, fasting, exercise, awareness, differences in sample criteria and the test used. Keywords: reaction time, response time, basketball, volleyball Abstrak: Olahraga basket dan voli merupakan olahraga yang memiliki beberapa kesamaan dalam gerak teknik dan membutuhkan reaksi yang cepat dalam permainannya. Penulisan literature review ini bertujuan untuk mengetahui manfaat perbedaan waktu reaksi antara pemain voli dan pemain basket. Metode yang digunakan adalah metode narrative review, yaitu dengan menggunakan artikel yang didapat melalui proses pencarian literatur. Penulisan dilakukan dengan menganalisis literatur terkait yang didapatkan dari hasil pencarian di PubMed dan Google Scholar. Artikel yang disertakan menggunakan bahasa Inggris dan dipublikasikan tahun 2009-2020. Sebanyak 5 artikel disertakan dalam literature review ini. Berdasarkan kelima artikel tersebut terdapat perbedaan waktu reaksi yang signifikan antara pemain voli dan pemain basket, dengan nilai waktu reaksi lebih cepat pada pemain basket. Signifikan atau tidak perbedaan waktu reaksi dipengaruhi oleh beberapa faktor yaitu semangat pemain, usia, intensitas latihan, kelelahan, puasa, olahraga, kesadaran, perbedaan kriteria sampel dan test yang digunakan. Kata-kata kunci: waktu reaksi, waktu respon, basket, voli